Diagnosis dan Penatalaksanaan Penyakit Arteri Perifer - Christi Natalia Sirait; Syazili Mustofa (MAJORITY, 2021)
Peripheral artery disease (PAD) is one of the most prevalent conditions, and it frequently coexists with vascular disease in other parts of the body. Early diagnosis is important for improving the patient’s quality of life and for reducing the risk of serious secondary vascular events such as acute myocardial infraction (AMI) or stroke. The best noninvasive measure for identifying the presence of occlusive arterial disease is the ankle-brachial index. Lower extremity PAD most frequently presents with pain during ambulation, which is known as “intermittent claudication”. Some relief of symptoms is possible with exercise, pharmacotherapy, and cessation of smoking. The occurrence of PAD is caused by insufficiency in the arteries due to the occurrence of the atherosclerosis process. Aspirin inhibits platelet synthesis through irreversible acetylation of cyclooxygenase (COX) enzymes on platelets. Because platelets do not have a nucleus, platelets are not able to form (COX) enzymes during their lifetime. As a result, the synthesis of thromboxane A2 (TXA2) which plays a major role in platelet aggregation is inhibited. Thus, long-term aspirin in the long term can prevent myocardial infarction and PAD.